Вопрос:

Вычислите (216*6^(-5))^3*(36^(-2))^(-1).

Ответ:

\[\left( 216 \cdot 6^{- 5} \right)^{3} \cdot \left( 36^{- 2} \right)^{- 1} =\]

\[= \left( 6^{3} \cdot 6^{- 5} \right)^{3} \cdot \left( \left( 6^{2} \right)^{- 2} \right)^{- 1} =\]

\[= \left( 6^{- 2} \right)^{3} \cdot \left( 6^{- 4} \right)^{- 1} = 6^{- 6} \cdot 6^{4} =\]

\[= 6^{- 2} = \left( \frac{1}{6} \right)^{2} = \frac{1}{36}\]

Похожие

© 2021 Copyright. Все права защищены. Правообладатель SIA Ksenokss.
Адрес: 1069, Курземес проспект 106/45, Рига, Латвия.
Тел.: +371 29-851-888 E-mail: [email protected]